Revitalization of the Language of Instruction and Interactive Multimedia in Elementary Schools - Putu Buddhi Prameswara; Ni Putu Kusuma Widiastuti (PT Bukuloka Literasi Bangsa, 2026)
The existence of regional languages is declining, especially within families. In fact, families are the main source of regional language acquisition for children. Therefore, the authors believe that this situation needs to be addressed. To address this, efforts need to be made through teaching. The first alternative, which is mainly from kindergarten to elementary school, is that regional languages can be used as the language of instruction. However, to implement the first effort, regional languages need to be further developed. Meanwhile, to implement the second effort, the focus of regional language teaching needs to be limited, in addition to the need to improve the quality of existing regional language teachers through technological development, one of which is interactive multimedia-based learning that is in line with the context of language use. The scope of this research is about the current condition of regional languages, ways to save regional languages, and teaching through interactive multimedia as a means of saving regional languages. The method used in this research is qualitative research. The collection technique is triangulation, data analysis is qualitative, and qualitative research results emphasize meaning rather than generalization regarding the revitalization of regional languages through the language of instruction and the application of interactive multimedia. The results of the study state that the application of regional languages as a language of instruction and the development of interactive multimedia can create learning experiences that provide opportunities for students to develop their regional language skills. Keywords: Regional Language, Teaching, Language of Instruction, Interactive Multimedia